The Representation of a Social Actor in the Legal Issue of a Jakartan Highway Accident (A Critical Discourse Analysis of News Reports of Rasyid Rajasa in Two TV Stations) - Okky Pertiwi (Universitas Pendidikan Indonesia (UPI), 2015)
The present study seeks to investigate the representations of Rasyid Rajasa regarding his highway accident in tvOne and RCTI news reports and the significance of the representations. This study employs a qualitative design with some measures of descriptive statistics and a perspective of CDA proposed by Fairclough (1995). The data include the selected four news reports of Rasyid Rajasa’s trial taken from youtube.com. The analysis uses theories of Transitivity and Thematization of Halliday (1994) in revealing the representations which signify underlying ideologies. The study reveals that Rasyid Rajasa is represented as guilty, a victim and as favored. From those representations, four ideologies are derived, namely democracy, capitalism, “fairness” in expressions and partiality in expressions. Keywords: Critical Discourse Analysis, Transitivity, Thematization, Social Actor, Representation.